A relação entre materialismo e consumo colaborativo - Santos, Paula Alexandra Baeta dos (2016)
Materialism is the importance assigned by the individual to the ownership and acquisition of material goods as a way to express personality and social identity. Collaborative consumption, in turn, corresponds to an alternate consumption mode in which the acquisition and ownership give way to practices arranged mainly around sharing and access. Given these definitions, there seems to be a conflict for more materialistic individuals when they consider adopting collaborative consumption practices. This study aimed to understand whether materialism is antecedent of propensity to adopt collaborative consumption practices. It also examined the relationship between materialistic individuals’ profiles and the importance attached to the reasons of adoption. For these purposes, a field survey with 223 telephone interviews was conducted with residents of the São Paulo metropolitan area. The reduced materialism scale developed by Richins (2004) and adapted by Ponchio and Aranha (2008) was used to measure this construct. The scale was validated in the context of this research. From the theoretical framework, four collaborative consumption modes were selected to be investigated: trading or selling used goods, renting or borrowing products, car rental and exchange of intangible goods (services). Similarly, the reasons for adoption were selected too. The results show that collaborative consumption is an option to be considered by more materialistic individuals, as long as it is not based on access, but in exchange or acquisition of used goods. One possible motivation for their engagement is the opportunity to acquire innovative products that contribute in some way to their social distinction. At the end, academic and managerial implications were discussed as well as the limitations of this study and recommendations for future research.